PENGARUH KONDISI OPERASI PADA PROSES PENGERINGAN KARAGENAN DENGAN FOAM - Verona Amelia; Bery Kristanti; Moh. Djaeni (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Foam mat drying is an option to speed up the drying process to maintain quality carrageenan. In this case, carrageenan mixed with egg white (albumin) as a foaming agent and methyl cellulose as a foam stabilizer. Carrageenan gel foam will break and create a porous structure so that a higher surface area for moisture transfer. Drying is carried out at various compositions (comparison agent and foam stabilizer), the air temperature and the thickness of the foam. Decrease in water content determined during the drying period. The results showed that the egg whites be stabilized with methyl cellulose can accelerate the rate of drying and drying time of carrageenan. Result show that at 80oC operating temperature and thickness of 2 mm carrageenan in the presence of egg whites 20% and 10% methyl cellulose, moisture diffusion and drying rate can be twiced compared with carrageenan drying without foam.